False Node Identification in VANETs for Inmproved Security - John, Neethu Maria; Kurian, Simy Mary; Vijayan, Vinodh P; George, Neema (International Journal of Computer Sciences and Engineering, 2025)
The best test of vehicular adhoc network is to distinguish the false node in the network. These false node can cause numerous perilous circumstances to the vehicles. The answer for this is the F measure based VANET.F measure bunch the se of hubs into groups and appoint a load to every hub in light of the contention in the network.The most noteworthy clash causing node set will get most elevated weight value and those node set will considered as false in the network. This permits the organization to identify bogus hubs all the more precisely with greatest accuracy and least review. Framework utilizes a half encryption strategy to lessen the time intricacies in the network. This assists with moving alongthe exactness and proficiency of the network